Fieldwork in Botswana: a Two-Page Checklist for Short-Term Researchers - Morrison, Monica (My University, 2021)
Recommendations for independent short term researchers carrying out fieldwork in Botswana.
Keywords: Research methdologies; Wildlife and Habitat Management; Communication